Penyuluhan dan Sosialisasi Tentang Pembuatan Permen Sapi sebagai Pakan Tambahan Ternak Ruminansia - Pramana, Angga; Hamzah, Farida Hanum; dihan, Dihan Kurnia; Wulantika, Trisia; Illahi, Ayu Kurnia; Kurniasih, Dedeh; Karmaita, Yummama; Sari, Deliana Andam; Chan, Sari Rukmana Okta Sagita; Situmorang, Helentina; Ramaiyulis, Ramaiyulis; Ningsih, Arum Rovarti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
Additional feed Forage is defined as feed that contains relatively higher crude fiber or undigested material. than concentrate. To achieve high livestock productivity, additional micro elements such as minerals and vitamins are required. Urea Molasses Block (UMB) is one type of supplement feed that contains these micro elements. This service partner is the Hasta Karya Jorong Solok Dalam Farmer Group. One of the things that can be done is by managing and utilizing Gambir Leaf Waste which is the residue from the extraction of gambier sap into something useful and useful as one of the ingredients in making cow candy. The purpose of this community service activity is to increase the participation of the Polytechnic. Payakumbuh State Agriculture in applying technology in accordance with the needs and conditions of farming communities in the field and adding insight and knowledge of farmer groups in making candy cows as additional feed for ruminants.